The Role of Transforming Growth Factor Beta (TGF-β) in Pelvic Organ Prolapse : A Systematic Review - Yulia Margaretta Sari; Bobby Indra Utama; Zelly Dia Rofinda; Aisyah Elliyanti (Fakultas Kedokteran Universitas Andalas, 2026)
Introduction: Pelvic organ prolapse (POP) is a gynaecological disorder with a rising prevalence, significantly affecting quality of life. While the pathogenesis of POP is multifactorial, alterations in the extracellular matrix (ECM) have been implicated, particularly the role of transforming growth factor-beta (TGF-β) in ECM remodelling. However, the precise relationship between TGF-β and POP remains unclear. Methods: A systematic review was conducted following PRISMA guidelines. Relevant studies were identified from PubMed, Scopus, Web of Science, and the Cochrane Library. Inclusion criteria focused on studies investigating TGF-β expression in women with POP. Data extraction included study design, patient demographics, TGF-β detection methods, and key findings. Results: Analysis of nine studies revealed mixed findings. Four studies reported a significant reduction in TGF-β1 expression in POP patients, suggesting impaired ECM regulation via the TGF-β1/Smad3 pathway. Three studies found no significant differences in TGF-β levels between POP and control groups, while one study linked increased TGF-β1 levels to severe prolapse, possibly as a compensatory response. Variations in methodology, sample size, and patient characteristics contributed to inconsistencies across studies. Conclusion: Current evidence suggests that TGF-β1 plays a role in POP pathogenesis, with lower levels potentially weakening ECM integrity and higher levels in advanced cases reflecting a failed reparative response. Further research is needed to explore TGF-β interactions with other biomarkers and assess its potential as a therapeutic target.